Antitumor Effect of Docetaxel in Osteosarcoma by the Inhibition of Wnt Signal Channel - Wang, D.-Z.; Gao, J.-F.; Jing, S.-F.; Wei, H.; Huang, X.-Y.; Li, C.-D. (Drug Research, 2015)
Osteosarcoma (OS) is the most common type of malignant bone tumor in adults and children. Despite the great strides in biology and medicine, the survival rate of patients with metastatic disease remains very poor. This rate has been staggering with recurrence and metastasis. In the present study, we proposed Wnt/β-catenin pathway as a key biological target for the effective treatment in OS. Wnt signaling has been reported to play important roles in osteoblastogenesis. We hypothesized that docetaxel (DTX) will effectively arrest the osteosarcoma progression by suppressing the Wnt/β-catenin pathway in OS cells. Our results show that DTX significantly inhibited the cell proliferation of U2OS and SaOS-2 cancer cells in a time-dependent and dose-dependent manner. DTX inhibited the intrinsic transcriptional activity of β-catenin/Tcf in U2OS cancer cells and SaOS-2 cancer cells. GSK-3βinhibitor (SB216763) treatment remarkably increased the β-catenin/Tcf transcriptional activities. The transcriptional activities have been increased by around ~200% due to the decrease in the degradation of β-catenin mediated through GSK-3β. Summarizing, present study clearly showed that DTX inhibited Wnt/β-catenin signalling pathways and significantly reduced the matrix metallopeptodase 9 (MMP-9) protein expressions and its activity. Taken together, our findings provide novel insight on the effect of anticancer small molecules to improve the outcomes in osteosarcoma.
Keywords: osteosarcoma; docetaxel; Wnt/β-catenin pathway; cell proliferation; MMP-9